Mechanical Characterization of Aluminium-Silicon-Titanium Diboride (Al-Si-TiB2) Reinforced by Scandium (Sc) and Strontium (Sr) - N.A. Basir, N.; H. Mustafa, N.; E. Ibrahim, R.; Rosmamuhamadani, R.; M. Mahat, M.; M. Yahaya, Sabrina; K. Talari, M. (International Journal of Engineering and Technology, 2019)
Aluminium based metal matrix composites (MMCs) have better properties and performance. They are commonly used in transport applications which require combinations of high strength and ductility. They are quite attractive due to their low density, capability to be strengthened by precipitation, good corrosion resistance, high thermal and electrical conductivity. Grain refinement plays a crucial role in improving characteristics and properties of aluminium-silicon (Al-Si) alloy. In this investigation, scandium (Sc) and strontium (Sr) elements were added to aluminium-silicon-titanium diboride (Al-Si-TiB2) alloy for refinement of grains. The compositions of 93 wt.% Al-Si, 6 wt.% TiB2, 0.5 wt.% Sc and 0.5 wt.% Sr were melted into induction furnace. Then the composites have been characterized on the mechanical properties and microstructure characterization. Instron tensile machine and vickers hardness tester were used to characterize the mechanical properties of the composite alloy. Microstructure and phase composition were characterized by Field Emission Scanning Electron Microscope (FESEM) and X-ray Diffraction (XRD). From the results obtained, addition of Sc and Sr, into Al-S-TiB2 improved the tensile strength and hardness of composite alloy. Results also showed that the inoculants addition able to enhance the refinement of grains and escalate the values of hardness and tensile strength of Al-Si-TiB2 composite. Mechanical properties related much on the microstructure as it can be seen that the addition of grain refiners produced much higher value of mechanical properties.Â Â